If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -7y = 17 Solving 11x + -7y = 17 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7y' to each side of the equation. 11x + -7y + 7y = 17 + 7y Combine like terms: -7y + 7y = 0 11x + 0 = 17 + 7y 11x = 17 + 7y Divide each side by '11'. x = 1.545454545 + 0.6363636364y Simplifying x = 1.545454545 + 0.6363636364y
| 3x^3-36x-6=0 | | 3x^4+8x^3-5x^2+16x-5=0 | | 7/2+1/2X=3X+3/2+5/2X | | B+12=25 | | x-5/3-4=x-1/2 | | 13=5z | | 32n^2-80n+50=0 | | 96=4(6)(3)+2(3)H | | 3x-41=19 | | X+1/4=10 | | 4v^2+20v-160= | | 3x/14-3=x/7+2 | | 56x-28x-25x-2=82 | | 2/3m+5/6m | | -3(3x-4)-(4x-4)+3=-9(x-6)-(9x+3)+2 | | x+(x*.06)=700 | | 2/3m+5/3m | | 96r+-97r+-38=25 | | X/8-16=9 | | 9(z+1)-2(z-4)=4(z-1)+2(z-3) | | z^2+6z=1 | | 3/2*-24=-36 | | 17.01/y=6.3 | | 8x+4x-11x=20 | | x+71=357 | | 26h+6h-15h-4h-5h-5=35 | | 8x-6x=12 | | 5/4*-18=-3 | | 2n-9=33 | | 7y-32y-19y+43y=-32 | | 2x-3/4x^5-6x-8/12x | | -3x+2(1-x)=0 |